Institutions for health care delivery - Serneels, P; Lievens, T (2008)
Most developing countries face important challenges regarding both the quality and quantity of health care they provide and there is a growing consensus that health workers play an important role in this. Although contemporary analysis of development emphasizes the central role of institutions, surprisingly little work looks at how institutions matter for health workers and health care delivery, which is the focus of this paper. One reason for the scarcity of work in this field is that it is unclear what the relevant theory is in this area. We carry out a formal exploratory analysis to identify both the problems and the institutional factors that offer an explanation. Using qualitative research on Rwanda, a country where health care problems are typical but where the institutional environment is dynamic enough to embody changes, we find that four institutional factors explain health worker performance and career choice. Ranked in order of ease of malleability they are: incentives, monitoring arrangements, professional norms and health workers’ intrinsic motivation. We discuss their role and the implications for future research.